Fabricate an 8.35-GHz frequency synthesizer - Attaran, A.; Ameri Mahabadi, H.; Moghavvemi, M. (2011)
The article presents information on designing a low-noise frequency synthesizer for achieving low-phase-noise outputs past 8 GHz for digital microwave radios (DMRs). These synthesizers can be used with the DMRs, depending on advanced digital modulation such as quadrature-amplitude-modulation (QAM) and quadrature-phase-shift-keying (QPSK) formats.